Factor Relating to Behaviour in Managing Disposable Mask Waste in The Harbour of Batan City - Novela Sari; Firdaus Yustisia; Suci Pahramida (Green Publisher Indonesia, 2024)
The harbour which is a public place has the potential as a place for disease transmission, environmental pollution, or other health problems. The objective of the current research was to determine the factors relating to behavior in managing disposable. This type of research is observational analytic using a cross sectional design. Simple random sampling technique and a sample of 90 respondents. The research instrument used a questionnaire and used the Chi Square test and logistic regression (α = 0.05). The results of the study showed that the most important factor related to the management of garbage masks are knowledge with (p value = 0.004; p < 0.05; OR = 6.571; 95% CI = 1.566-25.929), attitude (p value = 0.049; p < 0.05; OR = 3.388; 95% CI = 1.006-11.407), and binding regulations (p value = 0.002; p < 0.05; OR = 0.098; 95% CI = 0.022-0.434). The conclusions of the current research is that there is a significant relationship between knowledge, attitude and binding regulations with mask waste management.